Pengaruh Berkumur dengan Larutan Ekstrak Siwak (Salvadora persica) Terhadap pH Saliva Rongga Mulut - Tiara Adzakiyah; Indrawati Lipoeto; Nila Kasuma (Jurnal Sains Farmasi & Klinis, 2015)
Saliva is a complex body fluid and has important roles that related with biological processes in oral cavity. Saliva has important roles in maintaining health of oral cavity from caries diseases and periodontal diseases. One of saliva functions in maintaining oral health is associated with the degree of saliva’s acidity (pH). Salivary pH can influence oral health by related with caries diseases and periodontal diseases. One of preventive method could be done is chemically preventive by using mouth wash solution. One of natural mouth wash solution could be used is miswak (Salvadora persica) extract mouth wash solution. Chemical contents of Salvadora persica extract can prevent descending of salivary pH because it has bactericidal effect that will prevent acid production from oral bacteria, increase saliva buffer activity by increasing saliva secretion. The purpose of this study was to determine the influence of  Salvadora persica extract solution on salivary pH. The method used in this research is experimental with one group pre-posttest design. Subjects were 17 students of SMK Muhammadiyah 1 Padang. Measurements before and after mouth rinsing with Salvadora persica extract solution 50% performed on the subjects. The data were analyzed by paired T-test (p<0,05). This research showed the average salivary pH before given Salvadora persica extract solution was 6,565 and the average salivary pH after given miswak extract solution was 7,4. Mouth rinsing with Salvadora persica extract solution can increase salivary pH and can be used as mouth wash solution to maintain oral health.